Acute nutritional muscular dystrophy and mortality associated with selenium deficiency in artificial rearing of dairy calves in Salta, Argentina - Colque Caro, Luis Adrián; Medina, Diego M.; Avellaneda Cáceres, Agustín; Aguirre Castro, Laura Sabrina; Sandoval, Gabriela Virginia; Micheloud, Juan Francisco (Ediciones INTA, 2024)
Selenium (Se) is a trace element important for performance and immune functions in cattle. The deficiency of this mineral is widely distributed in northwestern Argentina and it is usually associated with intensive production systems. Calves seem more susceptible due to the metabolic regulation failures produced by this deficiency. This paper aims to describe a case of acute muscular dystrophy associated with Selenium deficiency in seven calves from a dairy farm in Salta, Argentina between March and May 2022. Selenium levels in the animals’ whole blood revealed that 66% of the calves (68,31±10,52 ppb) and approximately 90% of the cows (post-partum=71,24±10,04 ppb, and pre-partum 97,68±36,35 ppb) presented severely deficient values. The animals showed dehydration, weakness, prostration, respiratory signs, and even death without perceptible clinical signs. Macroscopically, diffuse pallor was found in the muscles of the hind limbs and in the myocardium in certain cases. Microscopically, severe polyphasic degeneration and necrosis of the muscle fibers were found, consistent with acute muscular dystrophy.